Prevalence of Hepatitis B and C virus infection among alcoholic individuals: importance of screening and vaccination - Cortes, Vanessa Faria; Taveira, Angela; Cruz, Helena Medina; Reis, Amanda Alves; Cezar, Jéssica Silva; Silva, Brener Santos; D’Assunção, Cintia Feliciano; Lampe, Elisabeth; Villar, Livia Melo (Revista do Instituto de Medicina Tropical de São Paulo, 2017)
Drug users have been reported to have an increased risk for acquisition of viral hepatitis. This study aims to evaluate the prevalence of HBV and HCV infection and usefulness of saliva for HBsAg and anti-HCV detection in alcoholic patients.A total of 90 alcoholic patients were recruited in 2013. HBsAg and anti-HCV were tested in serum and saliva, anti-HBc and anti-HBs were tested in serum using commercial enzyme immunoassays (EIA).Using serum samples, anti-HCV, HBsAg, anti-HBc and anti-HBs prevalences were 5.6%, 0%, 15.7%, and 29.2%. HBsAg detection in saliva showed 100% of specificity and anti-HCV detection demonstrated 100% of sensitivity and 94.7% of specificity. Low prevalence of HBV and high prevalence of anti-HCV were found and reinforced the recommendation of HBV vaccination to avoid the acute and chronic cases and HCV screening in this group to identify cases for antiviral therapy. Saliva samples could be used for anti-HCV detection in this population, what could increase the diagnosis access.